STRATEGI DINAS PERHUBUNGAN KOTA PAYAKUMBUH DALAM MENINGKATKAN RETRIBUSI PARKIR - Nova Yarsina; Rahmad Rahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to determine what factors can affect the increase in Local Revenue (PAD) of Payakumbuh City from Parking Retribution from the Payakumbuh City Transportation Service and. Knowing the strategy of the Payakumbuh City Transportation Service in increasing Parking Retribution. This research consists of 2 stages, namely the Delphi method with 2 stages of interviews and SWOT analysis, to obtain information on the factors that influence the increase in parking fees and see the level of importance and effectiveness of the government's response. Informants are experts (Experts) as many as 6 people and conduct a SWOT analysis to determine the right strategyThe findings of this study are: Several factors that influence the increase in parking fees, seen from Strengths. Based on the highest level of importance, policies related to parking are in the hands of the transportation service with an average score of 4.83 or 96.67 with the criteria of Very Important and Commitment regional heads and ranks with an average score of 4.83 or 96.67 with the criteria of Very Important. Based on the level of effectiveness of the government's response is Cooperation with other agencies with an average score of 3.83 or 76.67 with the criteria of Fairly Effective, Weaknesses Factors. Based on the highest level of importance, sanctions are less strict on judges and supervisors who violate the rules with an average score 5.00 or 100 with criteria Very Important . Based on the level of effectiveness of the government's response, sanctions are less stringent on judges and supervisors who violate the rules with an average score of 4.17 or 83.33 with Effective criteria. Opportunities Factor Based on the highest level of importance is the creation of a sense of security and comfort by the government towards the community with an average score of 5.00 or 100 with the criteria of Very Important. Based on the level of effectiveness of the government's response is the advancement of information technology with an average score of 4.17 or 83.33 with the criteria of Effectiveness and Threaths. Based on the highest level of importance is thuggery and unscrupulous officers with an average score of 4.83 or 96.67 with the criteria Very important. Based on the level of effectiveness of the government's response is natural conditions (pandemic) with an average score of 4.17 or 83.33 with Effective criteria. The results of the SWOT analysis are increasing the number of parking points, making clear SOPs and administration, increasing available facilities and infrastructure, utilizing information technology, establishing cooperation with other parties, transportation agency policies and local government commitments to curb illegal parking, working with security forces and related parties to take action against thuggery, unscrupulous officers and environmental social disturbances, Commitment of the Regional Head and his staff to increase tourism while taking into account natural conditions (Pandemic), Maximizing supervision and providing firm action / sanctions against parking attendants, Increasing the amount of parking budget, Establishing a minimum deposit parking fees and guarantee the security of official parking attendantsKeywords: strategic management, regional income, parking fees, delphi method, SWOT analysis